Factors relating to the nutritional status of toddlers in 2021 - Armus, Andi Mutiah; Darmawansyih, Darmawansyih; Kaharuddin, Andi Tihardimanto (Universitas Ahmad Dahlan, 2024)
Toddlers are the age group that most often suffers from malnutrition, which can be assessed by measuring their nutritional status. The nutritional status of a toddler is closely linked to various factors, including the mother’s level of education, the parents’ occupations, and the family’s income. This study aims to determine the factors related to the nutritional status of children under five in the Village of Untia, District of Biringkanaya, Makassar, in 2021. The first factor is the mother’s level of education, the second is the parents’ occupations, and the third is the family’s income. This research is an observational study using a cross-sectional approach, focusing on identifying the factors that influence the nutritional status of toddlers. The study sample consisted of 100 participants selected through purposive sampling. Data were collected through interviews and questionnaires filled out by the parents of the toddlers. Nutritional status was measured based on anthropometric BB/U compared with the WHO_NCHS Z-score values. Data analysis was performed using univariate and bivariate analyses. The results showed that the statistically significant factor influencing the nutritional status of children was family income (p-value = 0.000). Mothers' education level (p-value = 0.920) and the parents’ occupations (p-value = 0.622) were not significant factors. It can be concluded that one of the key factors influencing the nutritional status of children is the parent’s income. Higher-income families can provide better nutrition, while lower-income families may struggle, increasing the risk of malnutrition and health issues. Therefore, the economic well-being of parents is crucial in ensuring optimal nutrition and development for children.